2002
DOI: 10.1074/jbc.m206685200
|View full text |Cite
|
Sign up to set email alerts
|

The Stereoenantiomers of a Pinacidil Analog Open or Close Cloned ATP-sensitive K+ Channels

Abstract: ATP-dependent K؉ channels (K ATP channels) are composed of pore-forming subunits Kir6.x and sulfonylurea receptors (SURs). Cyanoguanidines such as pinacidil and P1075 bind to SUR and enhance MgATP binding to and hydrolysis by SUR, thereby opening K ATP channels. In the vasculature, openers of K ATP channels produce vasorelaxation. Some novel cyanoguanidines, however, selectively reverse opener-induced vasorelaxation, suggesting that they might be K ATP channel blockers. Here we have analyzed the interaction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Another agent used in the present study, P1075 is a more potent analogue of pinacidil (Lange et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…Another agent used in the present study, P1075 is a more potent analogue of pinacidil (Lange et al, 2002).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similar results were obtained under normoxic conditions with 1 μM UDCA. To further evaluate potential molecular targets responsible for the UDCA-mediated negative shift (hyperpolarisation) in membrane potential observed in human fetal fibroblasts, selective K ATP channel agents were employed (Lange et al, 2002). Addition of K ATP channel agonists induces efflux of K + from the cells, lowering the membrane potential to more negative values Lange et al, 2002;Shibukawa et al, 2005).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…However, amphiphilic inhibitors with weaker affinity show unblocking of K ATP channels in the whole‐cell configuration with a time course of 1–5 min and without apparent sigmoidicity. For example, the unblocking of K IR 6.1/SUR2B from PNU96296 (Lange et al. , 2002) and K IR 6.1/SUR2B from the glibenclamide congener, HMR 1883 (100 µmol·L −1 ; Russ et al.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has also been demonstrated that the enantiomers of a K ATP channel modulator PNU‐94750 affected channel activity and coupling to MgATP in opposite directions with the ( R )‐enantiomer inhibiting SUR2–Kir6.2 channels whereas the ( S )‐enantiomer behaving as a weak opener. Interestingly, these opposite effects were apparently mediated by binding to the same site on the sulfonylurea receptor (Lange et al ., 2002).…”
Section: Introductionmentioning
confidence: 99%